Tuberculosis in the Western Pacific Region: Estimating the burden of disease and return on investment 2020-2030 in four countries - Janne Estill; Tauhid Islam; Rein M.G.J. Houben; Jamie Rudman; Romain Ragonnet; Emma S. McBryde; James M. Trauer; Erol Orel; Anh Tuan Nguyen; Kalpeshsinh Rahevar; Fukushi Morishita; Kyung Hyun Oh; et al. (Elsevier, 2021)
Background: We aimed to estimate the disease burden of Tuberculosis (TB) and return on investment of TB care in selected high-burden countries of the Western Pacific Region (WPR) until 2030. Methods: We projected the TB epidemic in Viet Nam and Lao People's Democratic Republic (PDR) 2020-2030 using a mathematical model under various scenarios: counterfactual (no TB care); baseline (TB care continues at current levels); and 12 different diagnosis and treatment interventions. We retrieved previous modeling results for China and the Philippines. We pooled the new and existing information on incidence and deaths in the four countries, covering >80% of the TB burden in WPR. We estimated the return on investment of TB care and interventions in Viet Nam and Lao PDR using a Solow model. Findings: In the baseline scenario, TB incidence in the four countries decreased from 97•0/100,000/year (2019) to 90•1/100,000/year (2030), and TB deaths from 83,300/year (2019) to 71,100/year (2030). Active case finding (ACF) strategies (screening people not seeking care for respiratory symptoms) were the most effective single interventions. Return on investment (2020-2030) for TB care in Viet Nam and Lao PDR ranged US$4-US$49/dollar spent; additional interventions brought up to US$2•7/dollar spent. Interpretation: In the modeled countries, TB incidence will only modestly decrease without additional interventions. Interventions that include ACF can reduce TB burden but achieving the End TB incidence and mortality targets will be difficult without new transformational tools (e.g. vaccine, new diagnostic tools, shorter treatment). However, TB care, even at its current level, can bring a multiple-fold return on investment. Funding: World Health Organization Western Pacific Regional Office; Swiss National Science Foundation Grant 163878.